THE DIFUSI INOVASI ASESMEN PROFIL PELAJAR PANCASILA BERBASIS WEBSITE ALTERNATIF ASESMEN MATA KULIAH PENDIDIKAN PANCASILA - Abdinur Batubara; Ramsul Nababan; Maryatun Kabatiah; Fazli Rachman; Samadam Boangmanalu (Akademika : Jurnal Teknologi Pendidikan, 2023)
Research examining the creation of a sophisticated website-based assessment of Pancasila student profiles to be used as an alternative assessment in Pancasila Education lectures. By making this assessment, it is intended that students are consistently enthusiastic about always checking the quality of their Pancasila student profile. This research uses qualitative research methods with a realist ethnographic research design. This research raises the theme of the diffusion of innovations in website-based Pancasila student profile assessment applications using the forward chaining method, or the abbreviation D3P (Pancasila Student Profile Detection). The research was carried out in the sports science department, Faculty of Sports Science, Medan State University. The population of this research is students majoring in sports science at the Faculty of Sports Science, Medan State University, with a class D class of 2022 as a sample. The research design uses a realist ethnographic research design. Data will be collected using a questionnaire as a data collection tool. The data obtained will be analyzed using Miles and Huberman analysis techniques. The research results show that the D3P application in terms of components and quality has met the requirements based on expert validation assessments, and while the level of satisfaction with use by students was obtained, a percentage figure of 84% of students rated the D3P application as satisfactory. Then, an assessment by the third party, namely lecturers who were selected to represent a sample of realist ethnographic research designs, obtained 87.33% of the data, and the D3P application was categorized as good for consistently being used by students in detecting their Pancasila student profile.